P-163 Dysregulation of Star-Related Lipid Transfer Domain Protein (StarD7) Function Alters Intestinal Epithelial Barrier Function and Susceptibility to Experimental Colitis. (March 2016) - Hogan, Simon; Wu, David; Yang, Li; Weaver, Tim
Abstract : Background: The inflammatory bowel diseases (IBD) Crohn's disease (CD) and ulcerative colitis (UC) are chronic relapsing gastrointestinal (GI) inflammatory diseases that affect 1 to 1.5 million Americans and cause substantial morbidity and decreased quality of life. While the etiologies of IBDs remain unclear, experimental and clinical studies indicate that dysregulation of intestinal epithelial barrier function leading to an aberrant intestinal inflammatory response associated with exaggerated T-cell and macrophage (MØ's) activation is pathognomonic of disease. We have recently identified dysregulated expression of the protein, Star-related lipid transfer domain protein (StarD7) in colonic biopsy samples of inflamed UC patients. The inflammatory bowel diseases (IBD) Crohn's disease (CD) and ulcerative colitis (UC) are chronic relapsing gastrointestinal (GI) inflammatory diseases that affect 1 to 1.5 million Americans and cause substantial morbidity and decreased quality of life. While the etiologies of IBDs remain unclear, experimental and clinical studies indicate that dysregulation of intestinal epithelial barrier function leading to an aberrant intestinal inflammatory response associated with exaggerated T-cell and macrophage (MØ's) activation is pathognomonic of disease. We have recently identified dysregulated expression of the protein, Star-related lipid transfer domain protein (StarD7) in colonic biopsy samples of inflamed UC patients. Methods: To begin to define the contribution of StarD7 to the pathogenesis of IBD, we performed a series of ex vivo and in vitro analyses with intestinal epithelial-specific and global StarD7-deficient mice and employed murine models of colitis (Dextran sodium sulphate [DSS]), intestinal epithelial cell lines and siRNA StarD7 knockdown technology. Results: We show that ShhCreStarD7fl/fl mice have altered homeostatic intestinal epithelial barrier dysfunction compared with WT mice (Resistance RT 167.1 ± 8.1 versus 125.5 ± 5.6 W/cm 2 ; mean ± SEM, P < 0.05; FITC-Dextran 4kDa Flux 2.7 ± 0.2 versus 4.4 ± 0.3 pg·mL −1 ·min −1 ; mean ± SEM, P < 0.01; WT versus ShhCreStarD7fl/fl, respectively). Notably, the dysregulation of intestinal epithelial barrier function was associated with altered TJ protein expression including Claudin-4 and claudin-5 and increased susceptibility to DSS-induced colitis (histological score: 3.5 ± 0.9 versus 8.6 ± 1.0; mean ± SEM, P < 0.05; WT versus Shh Cre StarD7 fl/fl, respectively). In a series of in vitro experiments we identified novel critical functions for StarD7 in maintenance of (1) intestinal epithelial homeostatic mitochondrial function and (2) PPAR:RXR transcription factor function which culminates in preservation of TJ protein expression and intestinal epithelial barrier function. Moreover, we show that StarD7 knockdown in human intestinal epithelial cells promotes mitochondrial stress, which was associated with altered intestinal epithelial tight junction (TJ) protein expression, epithelial barrier dysfunction and increased pro-inflammatory cytokine (IL-25, IL-33 and TSLP) production. Indeed, rescue of mitochondrial stress by pharmacological agonist rescued intestinal TJ expression and barrier function. Conclusions: These data suggest a novel protective pathway, centered on the lipid transfer protein Stard7, which promotes epithelial barrier formation and maintains immune homeostasis.